(3GdYhGUe hGdbhGUes - (3eMeO Hf EHQGgje Hf Ydj Hf GdeQJVj Hf GdeaVd GdMSfj GdbGSej, CHh YHO Gddg, YR GdOjf, ef Bd GdhRjQ,J (B840 (3g` s
(3ChdgG (B:s
(3Gdhge GdNGeS YTQ bGd Ef GdJTHjg eSJjaV Yf CMeO Hf MfHd hbUO HPdc GdbOM ai cJH GdMOjK Hchfg ef QLGdge ceG bOM ajgG Hchf GdTGaYi hGdHNGQi ef QLGdge s
(3BNQgG (B:s
(3hbhd GdeYJRdg adG JbWY Ydi GdeNGda ajg HGdYfGO hJhge GdHGWd hGdaSGO ceG jhge GdSjO QMeg Gddg JYGdi Je gPG GdeLdO GdGKfi hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG eMeO GdCejf hYdi Bdg GdWjHjf GdWGgQjf hSde s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdNW GdSejcs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds